A beautiful time [compact disc] - Nelson, Willie, 1933- (Legacy, 2022)
Willie Nelson is back with his 72nd solo studio album. A full-fledged album of new studio material produced with longtime collaborator Buddy Cannon, it will come on his 89th birthday and shows off just how prolific he continues to be. The album includes some of his finest songwriting and performances in years. The 14 tracks include 5 amazing new Willie Nelson/Buddy Cannon compositions, new songs from Chris Stapleton and Rodney Crowell and a cadre of top Nashville songwriters, and a couple of plum covers by Leonard Cohen and the Beatles given expert interpretation by Willie.